# Systems of linear equations worksheets

Find out below how you can print this worksheet about solving systems of linear equations.

 Name: _________________________ Date: _______________________________

Find the solution for each system below by elimination or by substitution.

 1.y = 2x - 3y = x - 1x = ________   y = ___________ 2.y  =  -2x + 1y = 2x - 3x = ________   y = ___________

 3.4x - 2y = 82x + 2y = 4x = ________   y = ___________ 4.-2x - y = -22x + 4y = 11x = ________   y = ___________

 5.6x + 2y = 103x + 3y = -13x = ________   y = ___________ 6.7x - 12y = -135x + 4y = 19x = ________   y = ___________

 7.4x + 2y = 147x - 3y = -8x = ________   y = ___________ 8.15x + 3y = 910x + 7y = -4x = ________   y = ___________

 Name: _____________________________ Date : ______________________________

Tell whether the system below has 1 solution, no solution, or infinitely many solutions. If the system has a solution, find it.

 1. y = 6x + 1y = 6x - 1________________ 2. y = 3x + 1y = 2x - 1________________

 3. y = -5x + 1y = -5x + 1________________ 4. y = 8x - 5y = -8x - 5________________

 5. 2y - 6x = 10 2y + 6x = -10________________ 6. 10y = 20x + 4010y = 20x + 10________________

 7. y = (1/5)x - 2 5y + 10 = x________________ 8. y = (1/4)x + 6 4y - 24 = -x________________

## Recent Articles 1. ### Basic Math Review Game - Math adventure!

May 19, 19 09:20 AM

Basic math review game - The one and only math adventure game online. Embark on a quest to solve math problems!

Read More

New math lessons

Your email is safe with us. We will only use it to inform you about new math lessons. Tough Algebra Word Problems.

If you can solve these problems with no help, you must be a genius!

## Recent Articles 1. ### Basic Math Review Game - Math adventure!

May 19, 19 09:20 AM

Basic math review game - The one and only math adventure game online. Embark on a quest to solve math problems!

Read More

Everything you need to prepare for an important exam!

K-12 tests, GED math test, basic math tests, geometry tests, algebra tests. Real Life Math Skills

Learn about investing money, budgeting your money, paying taxes, mortgage loans, and even the math involved in playing baseball.